PENYELESAIAN SENGKETA HUKUM WARIS ANTARA HUKUM ADAT DAN HUKUM ISLAM DI (DESA MAUBASA TIMUR KECAMATAN NDORI KABUPATEN ENDE) - Susianti Ago; Ahmad Subekti; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
Abstract Indonesia has people of all kinds of religions, customs, and cultures, and has created a host of breakaway legal system, a system of western heirs, a system of islamic law, and a system of tribal heirs. Each of the legal systems of the heir is set in place. Because most indonesians are muslims, the system of inheritance is governed according to the islamic laws found in khi and its terms stemming from the qur 'an and the hadiths. Although the legacy of Islam is clear, its practices in society still do not socialize well. For more valid research, researchers have decoded it to an empirical type of research. Researchers picked up the research locations in the Muslim communities of maubasa east village, ndori district, ende flores, east southeast nusa. The reason for the location to be taken, first because it is here in its natural division that still applies to tribal laws. Second because of the large number of islamic societies, however, such customs are still used in inheritance division. The aim of this research is to describe the execution of the law of inheritance in the village of maubasa east, the division of inheritance according to hokum and islamic law, and the knowledge of the division of property according to customs and islamic law. To achieve that goal in the study is done with a qualitative type of repressive. Data collection procedures are conducted using observation methods of observation, interview methods of Tanya and documentative methods of records and photos. The results are (1) heir law in the village of maubasa east, The difference between the application is that a daughter has no inheritance from her parents because she has a husband and her husband is the one who has to support her family. (2) the appendage of property according to the hokum of custom and the law of Islam that a daughter of the middle child has no hold on to the hart of inheritance while the hokum of the deceased child is required by the islamic heir. Third, the child's position according to traditional law and islamic law is the same as a girl who has no part in making decisions because a woman is weak and easily exploited. Keywords: Customary, Female, Inheritance